2014
DOI: 10.1038/npp.2014.64
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal–Prefrontal BDNF and Memory for Fear Extinction

Abstract: Infusing brain-derived neurotrophic factor (BDNF) into the infralimbic (IL) prefrontal cortex is capable of inducing extinction. Little is known, however, about the circuits mediating BDNF effects on extinction or the extent to which extinction requires BDNF in IL. Using local pharmacological infusion of BDNF protein, or an antibody against BDNF, we found that BDNF in the IL, but not prelimbic (PL) prefrontal cortex, is both necessary and sufficient for fear extinction. Furthermore, we report that BDNF in IL c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
180
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(198 citation statements)
references
References 55 publications
13
180
4
1
Order By: Relevance
“…Our results indicate a similar requirement of the IL in the consolidation of recent and remote fear extinction and join the recent findings reported by Rosas-Vidal et al (2014) who showed similar effect of intra-IL microinfusion of brainderived neurotrophic factor (BDNF) in recent (1 day after conditioning) and remote (14 days after conditioning) extinction of fear memories. This corroborates previous results that we and others obtained regarding the crucial role of the IL subregion of the mPFC in the mediation of consolidation of recent fear extinction (Milad et al, 2004;Kritman and Maroun, 2012;Laurent and Westbrook, 2009;Sierra-Mercado et al, 2010) and extends it to remote fear memory.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results indicate a similar requirement of the IL in the consolidation of recent and remote fear extinction and join the recent findings reported by Rosas-Vidal et al (2014) who showed similar effect of intra-IL microinfusion of brainderived neurotrophic factor (BDNF) in recent (1 day after conditioning) and remote (14 days after conditioning) extinction of fear memories. This corroborates previous results that we and others obtained regarding the crucial role of the IL subregion of the mPFC in the mediation of consolidation of recent fear extinction (Milad et al, 2004;Kritman and Maroun, 2012;Laurent and Westbrook, 2009;Sierra-Mercado et al, 2010) and extends it to remote fear memory.…”
Section: Discussionsupporting
confidence: 92%
“…Using either reversible inactivation or protein synthesis inhibitor targeting the postretrieval consolidation phase (Akirav et al, 2006a;Eisenberg et al, 2003), we showed that the IL is involved in extinction consolidation of both recent and remote CFC as was recently shown (Rosas-Vidal et al, 2014). Targeting the same time window, the results show that the IL is involved only in extinction consolidation of recent, but not remote, COA.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Although studies of the effectiveness of therapeutics have generally used SEFL models other than restraint, a recent study showed that 7,8-dihydroxyflavone (7,8-DHF), a TrkB agonist, was able to rescue impaired extinction following restraint stress (Andero et al 2011). TrkB is a receptor for brain-derived neurotropic factor (BDNF), a regulator of neuronal plasticity that supports cognition and learning throughout life (Bramham and Panja 2014;Karpova 2014;Lu et al 2014) and can accelerate extinction in classical fear learning paradigms (Peters et al 2010;Rosas-Vidal et al 2014). The efficacy of this approach is likely to be tested in human studies because 7,8-DHF is safe and can cross the blood-brain barrier, and evidence supports the hypothesis that BDNF signaling is altered in PTSD patients (Dell'Osso et al 2009;Hauck et al 2010;Soliman et al 2010).…”
Section: Stress-enhanced Fear Learning Modelsmentioning
confidence: 99%